2021
DOI: 10.1097/bor.0000000000000853
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the molecular landscape of osteoarthritis in human tissues

Abstract: Purpose of review To provide an overview of recent developments in the field of osteoarthritis research with a focus on insights gleaned from the application of different -omic technologies. Recent findings We searched for osteoarthritis-relevant studies focusing on transcriptomics, epigenomics, proteomics and metabolomics, published since November of 2019. Study designs showed a trend towards characterizing the genomic profile of osteoarthritis-relevant tissues with high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The study found that over 140 genes were associated with OA and majority of the variants were localized in the non-coding region which made it inconspicuous. Hence, it is essential to establish the functional link between genomic and diseaserelevant alteration on multimolecular levels (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The study found that over 140 genes were associated with OA and majority of the variants were localized in the non-coding region which made it inconspicuous. Hence, it is essential to establish the functional link between genomic and diseaserelevant alteration on multimolecular levels (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory response and oxidative stress play key roles in the degenerative course of OA ( Tudorachi et al, 2021 ; Katsoula et al, 2022 ). It has been shown in several investigations that oxidative stress can cause articular cartilage dysfunction ( Ziskoven et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the tissues that make up the joint, cartilage, the subcondral bone, synovial capsule are essential in the determinism of the pathogenesis of osteoarthritis, characterized by the remodelling of the extracellular matrix in the inflammatory environment. Modern genetic typing approaches have allowed the identification of two types of osteoatritis and have provided the molecular sequence of two different tissue-specific osteoarthritis, allowing a better understanding of the etiopatogenesis of this disease [21]…”
Section: The Fundamental Components Of the Jointmentioning
confidence: 99%